Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Heather's solution for finding the distance between the points \( R(-3, -4) \) and \( S(5, 7) \) uses the distance formula correctly. Let’s review each step carefully to identify any potential mistakes:
1. The distance formula to find the distance \( d \) between two points \((x_1, y_1)\) and \((x_2, y_2)\) is:
[tex]\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
2. Substituting the given points \( R(-3, -4) \) and \( S(5, 7) \):
\( x_1 = -3 \)
\( y_1 = -4 \)
\( x_2 = 5 \)
\( y_2 = 7 \)
The correct substitution into the distance formula is:
[tex]\[ RS = \sqrt{(5 - (-3))^2 + (7 - (-4))^2} \][/tex]
3. Calculating the differences:
[tex]\[ 5 - (-3) = 5 + 3 = 8 \][/tex]
[tex]\[ 7 - (-4) = 7 + 4 = 11 \][/tex]
4. Substitute these results back into the formula:
[tex]\[ RS = \sqrt{8^2 + 11^2} \][/tex]
5. Simplify inside the radical:
[tex]\[ 8^2 = 64 \][/tex]
[tex]\[ 11^2 = 121 \][/tex]
[tex]\[ 64 + 121 = 185 \][/tex]
[tex]\[ RS = \sqrt{185} \][/tex]
Heather’s original work shows the following steps:
[tex]\[ \begin{aligned} RS & =\sqrt{((-4)-(-3))^2+(7-5)^2} \\ & =\sqrt{(-1)^2+(2)^2} \\ & =\sqrt{1+4} \\ & =\sqrt{5} \end{aligned} \][/tex]
From the correct calculations and seeing Heather's work, it is clear that Heather made a mistake in her initial substitution into the distance formula. She swapped the coordinates and used the wrong formula:
- She incorrectly calculated \( x_2 - x_1 \) as \( (-4) - (-3) \) instead of \( 5 - (-3) \).
- She incorrectly calculated \( y_2 - y_1 \) as \( 7 - 5 \) instead of \( 7 - (-4) \).
Thus, the answer is:
A. She substituted incorrectly into the distance formula.
1. The distance formula to find the distance \( d \) between two points \((x_1, y_1)\) and \((x_2, y_2)\) is:
[tex]\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
2. Substituting the given points \( R(-3, -4) \) and \( S(5, 7) \):
\( x_1 = -3 \)
\( y_1 = -4 \)
\( x_2 = 5 \)
\( y_2 = 7 \)
The correct substitution into the distance formula is:
[tex]\[ RS = \sqrt{(5 - (-3))^2 + (7 - (-4))^2} \][/tex]
3. Calculating the differences:
[tex]\[ 5 - (-3) = 5 + 3 = 8 \][/tex]
[tex]\[ 7 - (-4) = 7 + 4 = 11 \][/tex]
4. Substitute these results back into the formula:
[tex]\[ RS = \sqrt{8^2 + 11^2} \][/tex]
5. Simplify inside the radical:
[tex]\[ 8^2 = 64 \][/tex]
[tex]\[ 11^2 = 121 \][/tex]
[tex]\[ 64 + 121 = 185 \][/tex]
[tex]\[ RS = \sqrt{185} \][/tex]
Heather’s original work shows the following steps:
[tex]\[ \begin{aligned} RS & =\sqrt{((-4)-(-3))^2+(7-5)^2} \\ & =\sqrt{(-1)^2+(2)^2} \\ & =\sqrt{1+4} \\ & =\sqrt{5} \end{aligned} \][/tex]
From the correct calculations and seeing Heather's work, it is clear that Heather made a mistake in her initial substitution into the distance formula. She swapped the coordinates and used the wrong formula:
- She incorrectly calculated \( x_2 - x_1 \) as \( (-4) - (-3) \) instead of \( 5 - (-3) \).
- She incorrectly calculated \( y_2 - y_1 \) as \( 7 - 5 \) instead of \( 7 - (-4) \).
Thus, the answer is:
A. She substituted incorrectly into the distance formula.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.